The Role of Social Media in Promoting Indonesian Women’s Online Entrepreneurship: Prospects, Challenges and Strategies - Sri Wahyuningsih; Muhamad Mustaqim (IQTISHADIA, 2021)
Social media nowadays has been inevitably used by people in the world. It plays significant roles for human’s society including as the way of marketing and trading of products. The aim of this study was mainly to explore the prospects of using social media in driving and developing women’s entrepreneurship, its challenges and strategies. This present study anchored in a qualitative research. Data were garnered through semi-structured interviews to Indonesian women living in Kudus, Central Java, Indonesia running their online entrepreneurship as the additional job not the main ones. The results of the study revealed that the prospects of using social media cover it is beneficial for women’s entrepreneurship in improving sales and pursuing the innovation in their online business, it offers others to be reseller in a number of products and it allows the women to develop their online entrepreneurship. However, there are a number of challenges of using social media in online entrepreneurship including the emergence of negative comments and complaints about the products from costumers that will lead to decrease the reputation of business, poor connection of internet which may hinder a better business management, and the lack of knowledge about social media and team that can hinder these women entrepreneurs to handle their customers’ inquiries. Some strategies that need to be taken into account in online women’s entrepreneurship cover women entrepreneurs are supposed to upload new and up-to-date products, give best services to customers, collaborate with Shopee application (online shopping platform) in which they will get less risk in online business through its system and increase their innovation through online business class and trainings. The findings of the study offer an implication to the need of being innovative through the use of technology and social media in running online entrepreneurship particularly for women entrepreneurs since its flexibility and benefits as one of the ways to get additional income.